CODE MIXING PHENOMENON ON FOOTBALL PRESENTER’S UTTERANCES AT SCTV SPORTS PROGRAM - Nugroho, Heru (LANTERN (Journal on English Language, Culture and Literature), 2014)
Every human being has a certain way in communication. One of them is to communicate using another language to facilitate the listener to understand the message that is delivered. Code mixing is a phenomenon that often occurs in bilingual conversation, one of the examples of code mixing phenomenon can be found in sports program, especially in a football match program on television. This study is intended to determine and to explain the types and forms of code mixing that is often used by the presenters in presenting a program. The result of this study shows that the form of code mixing that is often used is the word insertion of outer code mixing, that is a mixing of a language with a foreign language because the football terms in English are more popular than the football terms in Indonesian.